(untitled) (Scientific journal of the Fergana State University, 2026)
In this article, the first boundary value problem is investigated for a three-dimensional elliptic equation with one singular coefficient. Based on the completeness property of systems of eigenfunctions of two one-dimensional spectral problems, the uniqueness theorem is proved. The solution to the problem is constructed as the sum of a double Fourier-Bessel series.